О размножении широконоски (Anas clypeata L.) на Горьковском водохранилище - Молодовский, А.В. (Вестник зоологии, 1972)
Reproduction of Anas clypeata L. was studied in the Unzhensky stationar in 1960 and 1961. A prenesting period lasted for 11-14 days, nesting for about two months. Anas clypeata L. makes nests on meadows, islands and plavni near nests of other species of ducks and snipes. A total period of egg-laying is 45--49 days. In complete ovipositions there are usually 5-13, more often 10 eggs. Incubation lasts for 22-23 days, hatching - for 22-49 days. Mass hatching takes place in the middle of June. Death loss of non-flying ducklings in broods accounts for 27.1-37%. The period of brood starting to fly takes 23_42 days. The greatest quantity of summer broods is observed in August. An average weight of hatched ducklings is 28.3 g; at the beginning of October maximum weight of four-month males is 600 g.